Enhanced PEDOT adhesion on solid substrates with electrografted P(EDOT-NH(2)) - Ouyang, Liangqi (Sci Adv, 2017)
Conjugated polymers, such as poly(3,4-ethylene dioxythiophene) (PEDOT), have emerged as promising materials for interfacing biomedical devices with tissue because of their relatively soft mechanical properties, versatile organic chemistry, and inherent ability to conduct both ions and electrons. However, their limited adhesion to substrates is a concern for in vivo applications. We report an electrografting method to create covalently bonded PEDOT on solid substrates. An amine-functionalized EDOT derivative (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanamine (EDOT-NH(2)), was synthesized and then electrografted onto conducting substrates including platinum, iridium, and indium tin oxide. The electrografting process was performed under slightly basic conditions with an overpotential of ~2 to 3 V. A nonconjugated, cross-linked, and well-adherent P(EDOT-NH(2))–based polymer coating was obtained. We found that the P(EDOT-NH(2)) polymer coating did not block the charge transport through the interface. Subsequent PEDOT electrochemical deposition onto P(EDOT-NH(2))–modified electrodes showed comparable electroactivity to pristine PEDOT coating. With P(EDOT-NH(2)) as an anchoring layer, PEDOT coating showed greatly enhanced adhesion. The modified coating could withstand extensive ultrasonication (1 hour) without significant cracking or delamination, whereas PEDOT typically delaminated after seconds of sonication. Therefore, this is an effective means to selectively modify microelectrodes with highly adherent and highly conductive polymer coatings as direct neural interfaces.